Isoliquiritigenin attenuates septic acute kidney injury by regulating ferritinophagy-mediated ferroptosis. Issue 1 (1st January 2021) - Tang, Yun; Luo, Haojun; Xiao, Qiong; Li, Li; Zhong, Xiang; Zhang, Jiong; Wang, Fang; Li, Guisen; Wang, Li; Li, Yi
Abstract: Defined differently from apoptosis, necrosis, and autophagy, ferroptosis has been implicated in acute kidney injury (AKI) such as ischemia-reperfusion injury induced AKI, folic acid caused AKI and cisplatin induced AKI. However, whether ferroptosis is involved in LPS induced AKI could be remaining unclear and there is still a lack of therapies associated with ferroptosis in LPS induced AKI without side effects. This study aimed to elucidate the role of isoliquiritigenin (ISL) in ferroptosis of LPS-induced AKI. We used LPS to induce renal tubular injury, followed by treatment with ISL both in vitro and in vivo . Human renal tubular HK2 cells were pretreated with 50 μM or 100 μM ISL for 5 h before stimulation with 2 μg/mL LPS. Mice were administered a single dose of either 50 mg/kg ISL orally or 5 mg/kg ferroptosis inhibitor ferrostatin-1 intraperitoneally before 10 mg/kg LPS injection. We found that LPS could induce mitochondria injury of renal tubular presented as the shape of mitochondria appeared smaller than normal with increased membrane density and are faction or destruction of mitochondrial crista through scanning electron microscope. Ferrostatin-1 significantly protected mice against renal dysfunction and renal tubular damage in LPS-induced AKI. ISL inhibited Fe 2+ and lipid peroxidation accumulation in LPS-stimulated HK2 cells. It also increased the expression of GPX4 and xCT, reduced the expression of HMGB1 and NCOA4 then attenuated mitochondria injury in renal tubular following LPS stimulation. These results indicated the potential role of ISL against ferritinophagy-mediated ferroptosis in renal tubular following LPS stimulation.